Digital Market Development with Artificial Intelligence in the Implementation of the Business Code of Ethics in Indonesia - Aulia Hanifah (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to analyze the influence of AI on the continued effectiveness of digital business processes and the implementation of digital business codes of ethics in Indonesia. This research was conducted using qualitative methods based on research references to test hypotheses. The research results show that advanced information technology, including AI, is able to increase the effectiveness of business processes with automation, personalization, and more effective marketing strategies, as well as the implementation of business codes of ethics, by increasing transparency, accountability, and community participation in business processes. However, the risk of violating the code of ethics is also higher and it is difficult to monitor the implementation of the code of ethics in business processes. This research explains that AI has a significant influence on the development of digital business process activities and the implementation of codes of ethics in digital business in Indonesia.